Effect of Internal Audit Function on Public Sector Accountability in Southwest, Nigeria - Akinleye, Gideon Tayo; Ogunmakin, Akinduro Adesola (The Journal of Accounting and Management, 2023)
This research analyzes the effects of the internal audit function on public sector accountability in the southwest of Nigeria, and specifically, the study assesses the impact of technical skills on public sector accountability in Nigeria, the Southwest. The study used primary data collected by administering the formal questionnaire. The results were obtained from a cross-sectional sample of public sector organizations, mostly local authority institutions. The population for the survey included the local authorities in Southwest Nigeria. Ondo State and Ekiti State were selected due to the availability of sufficient knowledge and ease of access. The data was analyzed using the multiple regression analysis method. The findings reveal that there is a negative and important 5% meaning association between INA and PAC dependent on standardized coefficients (-0.199) and the chance value (0.042). In addition, there is a large negative 5% COMP/PAC association dependent on standardized coefficients (-0.506) and a chance value (0.000). The analysis thus concluded that the internal audit service is insufficiently impartial to foster transparency in the public sector. This means that certain measures or method of intervention with the internal audit department’s operations still remain.